Final Project Portfolio Information System [Sistem Informasi Portofolio Tugas Akhir] - Alfan Rosid, Mochamad; Rukhi Alfian, Muhammad; Eviyanti, Ade (Indonesian Journal of Applied Technology, 2024)
The final project portfolio information system, developed in the form of a website built using the codeignter4 framework. This research aims to introduce the final project work of students in the form of a simple display with clear and structured content or information accompanied by a presentation video about the student's final project. This research has a research flow as a basis for managing and writing in this study. The result of this research is an information system that is web-based and can be accessed by all circles both from within the university or from outside the university, with features that can be used by users. with the increasing recognition of the work of students can be a value for students or for universities, making student final assignments as reference information is also a value in itself.